Polish Historiography of Polish - Lithuanian Union of 20th Century - Mečislovas Jučas (Lietuvos Istorijos Studijos)
Lithuania and Poland lived together for four hundred years. Two states were joined by the state's organization, common ruler and parliament (from 1569), family ties, language and customs, intellectual life, Catholic religion, and Church's organization. Although Lithuania's position was not relevant to Poland, the king lived in Poland, the Polish nobility was predominant in parliamentary life, furthermore, the Polish culture was much richer. The Lithuania and Poland two-sided state model was not only unique but also constant, strong, and even attractive. That is why the Poland-Lithuania union survived for a long period, and it is worth international attention. But it still is a domain of Polish historiography, which seeks to give answers for all questions concerning the union's stages: Krėva treaty in 1385, union of Lublin in 1569, reforms in 1791, and the end of the union too.